PENAKSIR RASIO REGRESI LINEAR UNTUK RATA-RATA POPULASI PADA SAMPLING ACAK SEDERHANA TANPA PENGEMBALIAN - Putri Susanti; Arisman Adnan; Harison ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
"> In this article we review three linear regression ratio estimators for the population mean on simple random sampling without replacement proposed by Singh et al. [Statistics in10 (2009) : 85 - 100 Transition, ]. These estimators are biased estimators and their mean square error are determined. The estimator with the smallest mean square error is the most efficient one. We apply these estimators to show the efficiencies of examples.